EXPLORING THE POTENTIAL ASSOCIATION BETWEEN DANDY WALKER SYNDROME AND ADIE'S PUPIL: A COMPREHENSIVE CASE STUDY AND SYSTEMATIC LITERATURE REVIEW - Salvatore Michele Carnazzo (Euromediterranean Biomedical Journal, 2023)
The purpose of this case report and literature review is to describe a case of Adie's pupil associated with variant Dandy-Walker complex (DWC) and to review the literature on the ocular manifestations of Dandy-Walker syndrome and variant Dandy-Walker syndrome. A literature search was conducted using the Pubmed database following the PRISMA guidelines. Inclusion criteria were radiologically confirmed Dandy Walker or Dandy Walker variant patients with ocular anatomical and functional anomalies. Overall, 48 studies met the inclusion criteria for this review, with a total of 634 patients diagnosed with Dandy-Walker syndrome and variant Dandy-Walker syndrome exhibiting a wide range of ocular manifestations. Microphthalmia was the most frequently reported abnormality, while megalocornea was less frequently reported. Of the 48 studies included, only one reported a case of Adie's pupil associated with variant Dandy-Walker complex, as presented in the case report. Ocular involvement in patients with Dandy-Walker syndrome and variant Dandy-Walker syndrome is rare. The authors present a case of variant Dandy-Walker complex associated with Adie's pupil, which has not been reported in the literature previously. The literature review confirms that ocular manifestations are rare but can occur in patients with Dandy-Walker syndrome and variant Dandy-Walker syndrome. Therefore, it is important for clinicians to evaluate patients with these malformations for possible ocular involvement